Analysis of Voluntary Disclosure Information on Social Media on The Behavior of Generation Z Investors - Gita Apsari Dewi; Dewa Gde Yoga Permana; Ni Luh Desi Wulandari (Jurnal Akuntansi Indonesia, 2026)
Abstract The development of digital technology has encouraged public companies to use social media as a medium for voluntary disclosure to improve transparency and communication with investors. However, the use of such information by Generation Z investors is influenced by their perceptions of technology acceptance. This study aims to analyze the effect of perceived usefulness and perceived ease of use on behavioral intention, as well as its impact on the use behavior of voluntary disclosure information on social media. This study lies in extending the Technology Acceptance Model by linking voluntary corporate disclosure on social media with Generation Z investors’ digital investment behavior in the Indonesian capital market context. This study applied a quantitative approach with an analytical survey design. Data were collected using a Likert-scale questionnaire distributed to 105 Generation Z investors in Indonesia and analyzed using SEMPLS. The results show that perceived usefulness and perceived ease of use positively and significantly affect behavioral intention. Furthermore, behavioral intention positively and significantly affects usage behavior. These findings confirm that technology acceptance factors play an important role in shaping Generation Z investors’ use of voluntary disclosure information on social media.